Antioxidant, anti-inflammatory and antimicrobial activity of natural products in periodontal disease: a comprehensive review - López-Valverde, Nansi; López-Valverde, Antonio; Montero, Javier; Rodríguez, Cinthia; Macedo de Sousa, Bruno; Aragoneses, Juan Manuel (Frontiers in Bioengineering and Biotechnology, 2023)
Periodontal diseases (PD) are common chronic inflammatory oral pathologies that are strongly linked to others not found in the mouth cavity. The immune system mediates the host response, which includes the up-regulation of proinflammatory cytokines, metalloproteinases, and reactive oxygen species (ROS); the latter may play an important role in the establishment and progression of inflammatory diseases, particularly periodontal disease, via the development of oxidative stress (OS). Natural antioxidants have powerful anti-inflammatory properties, and some can reduce serum levels of key PD indicators such tumor necrosis factor (TNF) and interleukin IL-1. This review compiles, through a thorough literature analysis, the antioxidant, anti-inflammatory, and antibacterial effects of a variety of natural products, as well as their therapeutic potential in the treatment of PD.